In-Class Interaction and Students’ Motivation in Intensive Course Classes - Maria Josephine Kriesye S (Widya Mandala Surabaya Catholic University, 2014)
This brief study is to see the relationship of peer interaction within class as well as the lecturer in-class attitude affected the students’ motivation and perception in a university education course where English is taught as a foreign language. The lecturers, each functioned as the language class instructor, managed a 100-minute-session in a class consisted of about twenty students ranged from 18 to 21 years old. The setting was the University of Widya Mandala Catholic University Surabaya in which a sort of matriculation program called Intensive Course becomes a compulsory subject for the freshmen. The hypothesis established confirmed that in-class lecturer’s attitude and the peer-interaction affect students’ motivation in learning, compared to the material content being exposed. A set of questionnaire was used as an instrument for data collection and distributed to the sample of class participants of Intensive Course program. It was hoped that the result would contribute beneficial findings that confirm whether interactions happened fostered the learning motivation of the class participants and how it affected them. Result showed that the hypothesis was verified to some extent as the students under study stated that the quality of their peer interaction was one of the grounds that contributed security feeling they need to have in order to freely participate in the learning process without having had to fear of making mistakes. The other ground which is also crucial is the trait of the lecturers that motivate them to persistently continue learning English, found to be challenging to most. Such trait is characterized as being understanding and friendly toward students. It is then hoped that the teachers of English as a Foreign language would realize the importance of having necessary teaching personality that accentuate their classes